The Japanese Pharmaceutical Industry: The New Drug Lag and the Failure of Industrial PolicyThe Japanese Pharmaceutical Industry: The New Drug Lag and the Failure of Industrial Policy, by ThomasL. G.. Cheltenham, UK: Edward Elgar, 2001. - Bogner, William C. (Academy of Management Review, 2002)
The article reviews the book “The Japanese Pharmaceutical Industry: The New Drug Lag and the Failure of Industrial Policy,” by L. G. Thomas.